Understanding sports coaching : the pedagogical, social and cultural foundations of coaching practice /: the pedagogical, social and cultural foundations of coaching practice. (2015) - Cassidy, Tania, 1964-; Jones, Robyn L; Potrac, Paul, 1974-
No abstract available